Analisis Karakteristik Gaya Belajar Vak (Visual, Auditorial, Kinestetik) Siswa Kelas X SMAK St. Petrus Ende Tahun Ajaran 2019/2020 - Norbertus Labu (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2021)
This research aims to describe the characteristics of the VAK (visual, auditory, kinesthetic) learning styles of students or learners. Learning style is a very important learning modality. Information relating to the characteristics of student learning styles is very important for the teacher so that the teacher can choose a fixed learning strategy, which will thus improve the quality of learning. Students will also more easily motivate themselves in learning. This research is non-experimental and classified as a qualitative analytical descriptive study. The subjects of this research were all students of class X SMAK St. Petrus Ende 2019/2020 school year. The instrument used in this research was a questionnaire filled out by research subjects. This learning style questionnaire was filled out by 189 students of class X of SMAK St. Petrus Ende 2019/2020 school year. The results of the analysis of the learning styles of class Xa students are dominated by auditory learning styles (50.00%). Class Xb is dominated by auditory learning styles (60.53%). Class Xc is dominated by auditory learning styles (68.42%). Class Xd is dominated by a combined visual and auditory learning style (37.84%). Class Xe is dominated by auditory learning styles (55.27%). Overall learning styles of class X students of SMAK St. Petrus Ende class of 2019/2020 is dominated by auditory learning style that is equal to 52.91%.